TEKNIK BUDIDAYA IN VITRO Eleutherine sp. (Bawang Sabrang) - Hoesen, Djadja Siti Hazar (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Vegetative propagation from bulb excised of Eleutherine sp. (Iridaceae) were culturedÃ‚Â in Murashige and Skoog (MS) medium supplemented with plant growth regulatorÃ‚Â (PGR) Benzyl adenine (BA) 1 mg/l at initiation stage, BA (2 and 5) mg/l for inducedÃ‚Â shoot buds formation at multiplication stage. In this study also BA 2 mg/l and BA 2 mg/lÃ‚Â combined with naphthalein acetic acid (NAA) 0.5 mg/l were treated for rooting planletsÃ‚Â formation. Calli formation were induced with auxin PGR picloram 1 mg/l combined withÃ‚Â 2,4 dichlorophenoxy acetic acid (2,4-D) 0.5 and 1 mg/l in concentrations. The mediaÃ‚Â contained 2 mg/l cytokinin (BA) without auxin (NAA), resulted the highest shoot budsÃ‚Â formation. Rooting planlets were produced in MS medium combined with BA and NAA.MS medium contains Picloram 1 mg/l and 2,4-D 1 mg/l was optimal for frequency oncalli initiation (100%) and the largest diameter of calli also represented in cultured MSÃ‚Â medium with picloram 1 mg/l and 2,4-D 1mg/l. In acclimatization stage, 100% of planletsÃ‚Â survived and successfully transplanted to soil medium in the field.Key words: in vitro, Eleutherine sp.